EL PATRIMONIO ARQUITECTÓNICO, SU IMPORTANCIA Y SUS APORTACIONES EN SU CONTEXTO HISTÓRICO Y POLÍTICO: La reutilización como una estrategia para la conservación - Velázquez, Miguel Navarro (UNIVERSIDAD DE SONORA, 2018)
The trace of man through the ages is evident in the works of art that he leaves as his heritage to the new generations.  Within these artistic expressions is architecture. It shows their time and their dreams, their forms and methods of life, their needs and aspirations of wanting to shelter under the stars within an appropriate space and prone to the development of the different activities of their era, their needs. With the desire to transmit its importance in history, as part of the life cycle that over the years, the millennia, have been commissioned to unite in the creation of a new link to complement the chain that represents the presence of man on this planet. The sun, the rain, the winds, in general the climate causes our constructions to expand, contract, move and suffer deformations and in some cases return to normal or die. Constructions are living entities, they are born, they have a useful life, they get sick and they can die. Some seem to challenge time and its inclemencies and stand proud and dignified over the centuries.  For this reason, architecture gives us through time a holistic image of its time in a specific place and in a specific community and thus we can know first-hand the dreams and pretensions of a people, of a community with the diversity of variants that this one could have had.  In the current era, with the existing culture, with the spatial needs to be solved, the problem represented by abandoned heritage buildings and in precarious and dangerous conditions, restoration is justified within a framework of active preservation, and reutilization for your conservation.